THE HISTORY OF QUILTING ART AMONG COUNTRIES OF EUROPE AND ASIA: THE HISTORY OF QUILTING ART AMONG COUNTRIES OF EUROPE AND ASIA - Nazirova, Nafisa (Журнал иностранных языков и лингвистики, 2021)
THE HISTORY OF QUILTING ART AMONG COUNTRIES OF EUROPE AND ASIA